Factorial structure and internal consistency of the Fatigue Severity Scale in Colombian population with chronic diseases (2017)
The present study has a psychometric design, with the objective of analyzing the factorial structure and the internal consistency for the Spanish version of the Fatigue Severity Scale (FSS) Questionnaire for Colombian population with chronic disease. Was applied the questionnaire to 52 people with chronic disease in Villavicencio city. The factorial Analysis indicates three factors: Factor 1 named physical affectation, Factor 2 named social affectation and Factor 3 named motivational affectation of the fatigue, where they explain the 76.324% of the total cumulative variance with .870 of Cronbach's Alpha. The results present a high reliability and concordance for the factorial structure with the original version which indicates an adequate validity of the test for Colombian population with chronic disease. © Servicio de Publicaciones - Universidad de Murcia.